Critical Care Management of Fracture Dislocation of Cervical Spine: A Case Report - Liliriawati Ananta Kahar; Wiwi Monika Sari; Aldhimas Marthsyal Pratikna; Arif Gunawan (HM Publisher, 2023)
Background: Spinal cord injuries affect nearly 1 million people every year, more than 90% of all cervical injuries require intubation, most cases also require tracheostomy, and nearly 40% are ventilator dependent. This study aimed to describe critical care management of fracture dislocation of spine. Case Presentation: A 27-year-old male patient complained patient came with complaints of weakness in both limbs 13 hours before admission. Initially, the patient was driving a motorbike then the patient was involved in an accident with a car after the incident, the patient also felt a bit short of breath, could not move both his leg and hand, and could not feel defecation or urination. Patient was diagnosed with Fracture dislocation of C4-C5. The patient underwent elective decompression stabilization. Patient admitted to ICU with the majority requiring assisted ventilation. After five days in the ICU, the patient was challenged to be released from the ventilator, so the patient was performed early tracheostomy Conclusion: Patients with cervical injuries require comprehensive care in the intensive care unit, especially in airway management and respiratory support, in addition to addressing the potentially catastrophic multisystem sequelae of nerve damage.